a) (x-1) (x+1)-x(x+2)=x-10
b)x(x+5)-(x-2)(x+9)=3(x+1)-1
Ajutorr!
a=2,4
b=15
Răspunsuri la întrebare
Răspuns de
1
a) (x-1) (x+1)-x(x+2)=x-10
x²-1 -x²-2x=x-10
-1 -2x=x-10
3x=9
x=3
x(x+5)-(x-2)(x+3)=3(x+1)-1
x²+5x-(x²-2x+3x-6)=3x+3-1
x²+5x-x²-x+6=3x+2
4x-3x=-6+2
x=-4
x²-1 -x²-2x=x-10
-1 -2x=x-10
3x=9
x=3
x(x+5)-(x-2)(x+3)=3(x+1)-1
x²+5x-(x²-2x+3x-6)=3x+3-1
x²+5x-x²-x+6=3x+2
4x-3x=-6+2
x=-4
a=2,4
b=15 la asta ma puteti ajuta? :>
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
x²-1 -x²-2x=x-10
-1 -2x=x-10
3x=9
x=3